Comparing electric heating systems at equal thermal comfort: An experimental investigation. (15th January 2018) - Léger, Jérémie; Rousse, Daniel R.; Le Borgne, Kilian; Lassue, Stéphane
Abstract: Electric heaters are still widely used for residential heating. It is often believed that electric systems all perform equally; however, this is not the case as diffusors distribute heat in different ways. In this study, an experimental investigation of electric heating systems shows that heat distribution can indeed influence the effectiveness of the equipment to maintain thermal comfort. A baseboard heater, a convector and a radiant heater are compared at equal thermal comfort conditions in a bi-climatic chamber at different cold room temperatures. To demonstrate the repeatability of the results, a statistical analysis is presented. Results show that the convector consumes less energy than the baseboard and radiant heaters despite achieving similar thermal comfort. Though only small differences were observed, the investigation shows that electric heating systems are not all equal in energy efficiency. There is thus an opportunity to improve the heating effectiveness by improving the heat distribution of the equipment. Highlights: A convection heater is found to be the most energy efficient system. Heaters are compared in bi-climatic chamber at equal thermal comfort. Heating systems that heat the window more are less energy efficient.